2016
DOI: 10.1186/s13002-016-0094-y
|View full text |Cite
|
Sign up to set email alerts
|

Wild food plants and fungi used in the mycophilous Tibetan community of Zhagana (Tewo County, Gansu, China)

Abstract: BackgroundThe aim of the study was to investigate knowledge and use of wild food plants and fungi in a highland valley in the Gannan Tibetan Autonomous Region on the north-eastern edges of the Tibetan Plateau.MethodsField research was carried out in four neighbouring villages in a mountain valley of the Diebu (Tewo) county, surrounded by spruce forests. The study consisted of 30 interviews with single informants, or group interviews (altogether 63 informants). Apart from collecting voucher specimens, we also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…Studies among the Tibetan communities in Gansu province of China have shown use of 54 wild vascular plant species for edible purposes. The mean and median of wild edible plants used in the area was 20.8 and 21, respectively [ 47 ]. In the present study, though total number of WEP species reported was comparatively low (50), mean of WEP used was higher (22.3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies among the Tibetan communities in Gansu province of China have shown use of 54 wild vascular plant species for edible purposes. The mean and median of wild edible plants used in the area was 20.8 and 21, respectively [ 47 ]. In the present study, though total number of WEP species reported was comparatively low (50), mean of WEP used was higher (22.3).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in Poljica and Krk islands, Croatia total number of wild edible species used was higher [ 48 ]. However, mean species used per interview was low [ 47 , 48 ]. It reveals that local people individually use more species in the present study area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The uses of 81 species of vascular plants were recorded in Tibetans of Zhouqu county, Gansu, China [5]. The uses of 54 species of vascular plants and 22 mushrooms were recorded in Tibetan community of Zhagana in Tewo County, Gansu, China [6].…”
Section: Introductionmentioning
confidence: 99%